Easier Done Than Said: Transnational Bribery, Norm Resonance, and the Origins of the US Foreign Corrupt Practices Act1. Issue 1 (15th August 2013) - Gutterman, Ellen
<x xml:space="preserve">Abstract</x> The US Foreign Corrupt Practices Act of 1977 (FCPA) is having an unprecedented moment. In 2010, corporations paid 1.8 billion in FCPA fines, penalties, and disgorgements—the most ever recorded in this controversial Act's history and half of all criminal‐division penalties at the Justice Department. While this recent pattern of enforcement is itself interesting, a deeper puzzle lies in the origins and early trajectory of the FCPA. Throughout the late 1970s and most of the 1980s, major US business groups opposed its unilateral ban on transnational bribery and lobbied the government to repeal this costly constraint on American businesses operating overseas. Yet, despite a decade of pressure from otherwise powerful groups, the government failed to respond to business demands amidst strategic trade concerns about the FCPA. Why? The paper applies a Constructivist lens, together with concepts from the theory of legal reasoning, to analyze the early history of the FCPA and explain its continued significance in US foreign economic policy. Anti‐corruption norm resonance and the pressure publicly to justify norm‐transgressing practices made foreign corrupt practices by American businesses "easier done than said."